Factors of forming tourist flows in modern development of tourism in the Russian Federation - I. I. Deren; A. D. Zemlyanikina (Вестник университета)
The article presents the factors of modern development of tourism in Russia. Statistics on the development of the Russian tourism indicate that the direction, dynamics and intensity of tourist flows have changed quite significantly from 2010 to 2022. According to certain development parameters of the domestic tourism industry, there are both considerable achievements and unresolved issues. The formulation of public policy on resolution of the latter should be implemented on the basis of current factors. Sustainable development of the Russian tourism sector is possible by ensuring an integrated approach that includes improvement of the quality of tourism services based on the principles of sustainable tourism alongside with increase of investment attractiveness of tourism infrastructure and increase of investments in tourism digital products. The expected promising directions for the development of the industry are substantiated: the priority of health and safety, ecotourism, decrease in the number of spontaneous trips, development of niche tourism areas, digitalisation of the industry, virtualisation and simulation (imitation of tourism activities). Attention is focused on important factors of tourism development: potential growth points for the tourism industry are identified as well as the expected types of tourism that will attract demand from tourists.